Independent evolution of satellite DNA sequences in homologous sex chromosomes of Neotropical armored catfish (Harttia) - Sassi, Francisco de M. C.; Garrido-Ramos, Manuel A.; Utsunomia, Ricardo [UNESP]; dos Santos, Rodrigo Zeni [UNESP]; Ezaz, Tariq; Deon, Geize A.; Porto-Foresti, Fábio [UNESP]; Liehr, Thomas; Cioffi, Marcelo de B. (Springer Nature, 2025)
The Neotropical armored catfish Harttia is a valuable model for studying sex chromosome evolution, featuring two independently evolved male-heterogametic systems. This study examined satellitomes—sets of satellite DNAs—from four Amazonian species: H. duriventris (X1X2Y), H. rondoni (XY), H. punctata (X1X2Y), and H. villasboas (X1X2Y). These species share homologous sex chromosomes, with their satellitomes showing a high number of homologous satellite DNAs (satDNAs), primarily located on centromeres or telomeres, and varying by species. Each species revealed a distinct satDNA profile, with independent amplification and homogenization events occurring, suggesting an important role of these repetitive sequences in sex chromosome differentiation in a short evolutionary time, especially in recently originated sex chromosomes. Whole chromosome painting and bioinformatics revealed that in Harttia species without heteromorphic sex chromosomes, a specific satDNA (HviSat08-4011) is amplified in the same linkage group associated with sex chromosomes, suggesting an ancestral system. Such sequence (HviSat08-4011) has partial homology with the ZP4 gene responsible for the formation of the egg envelope, in which its role is discussed. This study indicates that these homologous sex chromosomes have diverged rapidly, recently, and independently in their satDNA content, with transposable elements playing a minor role when compared their roles on autosomal chromosome evolution.